2021
DOI: 10.1158/1078-0432.ccr-21-0471
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pseudoprogression Following Lomustine–Temozolomide Chemoradiation in Newly Diagnosed Glioblastoma Patients Using FET-PET

Abstract: Purpose: The CeTeG/NOA-09 phase III trial demonstrated a significant survival benefit of lomustine–temozolomide chemoradiation in patients with newly diagnosed glioblastoma with methylated O6-methylguanine-DNA methyltransferase (MGMT) promoter. Following lomustine–temozolomide chemoradiation, late and prolonged pseudoprogression may occur. We here evaluated the value of amino acid PET using O-(2-[18F]fluoroethyl)-l-tyrosine (FET) for differentiating pseudoprogression from tumor progression. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Kebir et al noted that the mean and maximum tumor-to-brain (TBR) 18 F-FET uptake ratios were increased in patients with enhancing lesions which presented 3 months after completion of CRT, suggesting its value in the evaluation of PsP (148). In a recent study by Werner et al, the mean TBR calculated from 18 F-FET-PET showed the highest accuracy among static and dynamic 18 F-FET uptake parameters (149). In the post-BVZ setting, George et al showed that 18 F-FET uptake decreases after BVZ therapy and only moderately correlates with contrastenhanced T1 signal intensity; they also found that a high ratio of the 18 F-FET uptake before and after treatment as well as an increased correlation between 18 F-FET uptake and contrastenhancing signal were associated with poor PFS and OS (150).…”
Section: Amino Acid Pet Radiotracersmentioning
confidence: 99%
“…Kebir et al noted that the mean and maximum tumor-to-brain (TBR) 18 F-FET uptake ratios were increased in patients with enhancing lesions which presented 3 months after completion of CRT, suggesting its value in the evaluation of PsP (148). In a recent study by Werner et al, the mean TBR calculated from 18 F-FET-PET showed the highest accuracy among static and dynamic 18 F-FET uptake parameters (149). In the post-BVZ setting, George et al showed that 18 F-FET uptake decreases after BVZ therapy and only moderately correlates with contrastenhanced T1 signal intensity; they also found that a high ratio of the 18 F-FET uptake before and after treatment as well as an increased correlation between 18 F-FET uptake and contrastenhancing signal were associated with poor PFS and OS (150).…”
Section: Amino Acid Pet Radiotracersmentioning
confidence: 99%
“…FET-PET performed a mean of 10 (SD, 7) days after the equivocal MR imaging findings showed a high accuracy of 87% to identify pseudoprogression, with an improved specificity of 100%. 42 A combined analysis of arterial spin-labeled CBF and FDOPA uptake allowed high diagnostic performance in differentiating progression and pseudoprogression in treated gliomas. 43 Given the high sensitivity for identifying tumor progression, FET-PET MR imaging could change clinical management in nearly one-half of patients.…”
Section: Disease and Treatment Monitoring: Differentiation Betweenmentioning
confidence: 99%
“…This observation was consistent with those seen in several other studies utilizing dynamic AA PET. 24 , 26 , 28 In a later study, Werner et al diagnosed pseudoprogression with 87% accuracy using static [ 18 F]FET-PET in GBM patients treated with TMZ-lomustine RCT. The addition of dynamic parameter, TTP, further improved the diagnostic specificity and positive predictive value to 100%.…”
Section: Review Of Studiesmentioning
confidence: 99%
“… 34–36 In differentiating pseudoprogression from true progression, most studies utilized a TBR max threshold ranging from 1.9-2.3 with success. 18 , 25 , 28 , 31 In these studies, TBR values after treatment were used for diagnosis without comparison to pretreatment TBR. Similar to clinical outcome prediction, TBR max appears to be more accurate than TBR mean in diagnosing pseudoprogression.…”
Section: Review Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation